2010
DOI: 10.1002/joc.1990
|View full text |Cite
|
Sign up to set email alerts
|

European snow cover extent variability and associations with atmospheric forcings

Abstract: Snow cover in Europe represents an important component of the region's climatic system. Variability in snow cover extent can have major implications on factors such as low-level atmospheric temperatures, soil temperatures, soil moisture, stream discharge, and energy allocation involved in the warming and melting of the snowpack. The majority of studies investigating Northern Hemisphere snow cover identify European snow cover extent as a portion of the Eurasian record, possibly masking complexities of this subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Henderson and Leathers (2010) confirm the strong associations between large (small) snow cover seasons and the negative (positive) phase of the North Atlantic Oscillation.…”
Section: Discussionsupporting
confidence: 75%
“…Henderson and Leathers (2010) confirm the strong associations between large (small) snow cover seasons and the negative (positive) phase of the North Atlantic Oscillation.…”
Section: Discussionsupporting
confidence: 75%
“…Large-scale atmospheric circulation-and the NAO in particular-have been shown to be a strong determining factor of changing snow conditions in the Baltic Sea region. The large-scale circulation affects the extent of European snow cover (Henderson and Leathers 2010), snow amounts (Kohler et al 2006;Falarz 2007;Popova 2007;Bednorz and Wibig 2008), the occurrence of heavy snowfall (Bednorz and Wibig 2008) and snow cover duration (Klavins et al 2009). However, formal assessments of the ultimate causes, such as increasing atmospheric greenhouse gas concentrations, for changes in snow conditions are still rare.…”
Section: Hydrological Cyclementioning
confidence: 99%
“…A modelling study that eliminated snow cover from the climate system found that this resulted in higher mean annual surface air temperature; decreased soil temperature and increased permafrost extent; drying of upper-layer soils and changes in the annual cycle of run-off; and the disappearance of extreme cold air outbreaks (Vavrus 2007). Variability in SCE in Europe affects low-level atmospheric temperature, soil temperature, soil moisture, stream discharge and energy flow in the warming and melting of the snowpack (Henderson and Leathers 2010).…”
Section: Introductionmentioning
confidence: 99%